Translators on a Tight Rope: The Challenges of Translating Edwidge Danticat’s Breath, Eyes, Memory and Patrick Chamoiseau’s Texaco - N’Zengou-Tayo, Marie-José; Wilson, Elizabeth (TTR, 2000)
AbstractTranslators on a Tight Rope: The Challenges of Translating Edwidge Danticat's Breath, Eyes, Memory and Patrick Chamoiseau's Texaco — For Caribbean intellectuals and scholars, translation of Caribbean literary texts has a key role to play for breaching the language barriers in the Caribbean and fostering regional integration. However, most publishing houses are located in the industrialized North, i.e. in countries which had colonial interests in the region. The targeted market of these publishers is located in a region which tends to exoticize the Caribbean. Henceforth, translating Caribbean literature can be like walking on a tight rope, since the translator would have to negotiate carefully between exoticism and faithfulness to the Caribbean culture. In addition, at least for the Dutch, French and English-speaking Caribbean, there is also the issue of bilingualism: use of French in relation with use of Haitian / Martinican / Guadeloupian Creole, use of English with Jamaican / Trinidadian Creole or a French-based Creole (Dominica, Grenada, and St Lucia). Against this background, we examined two translations, one from English into French (Edwidge Danticat's Breath, Eyes, Memory, 1994), the other from French into English (Patrick Chamoiseau's Texaco, 1992). We analyzed the translators' strategies in order to convey the Haitian and Martinican cultures. We also discussed their rendering of the bilingual shifts present in both texts. One translator was more successful than the other, which also raised the issue of 'scholar' translation versus 'non scholar' translation. In conclusion, Caribbean academics have to be watchful of the translations of literary works of the region since these translations, which do not aim primarily at the regional audience will nevertheless impact on cultural relationships in the region.